2013
DOI: 10.1124/mol.113.085993
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alcohol-Sensitive Position in the N-Methyl-d-Aspartate Receptor GluN2A Subunit M3 Domain Regulates Agonist Affinity and Ion Channel Gating

Abstract: Abundant evidence supports a role for N-methyl-D-aspartate (NMDA) receptor inhibition in the behavioral actions of ethanol, but the underlying molecular mechanisms have not been fully elucidated. We recently found that clusters of five positions in the third and fourth membrane-associated domains (M3 and M4) at the intersubunit interfaces form putative sites of alcohol action. In the present study, we found that one of these positions, NMDA receptor subunit, GluN2A(F636), can strongly regulate ethanol sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Previous studies showed that ethanol inhibits NMDA receptors by altering ion channel gating, primarily by decreasing mean open time of the channel, and studies from our laboratory reported that mutations at ethanol-sensitive positions in the GluN2A subunit also strongly influence ion channel gating kinetics (Ren et al , 2003a; Ren et al , 2007; Ren et al , 2008; Honse et al , 2004; Ren et al , 2013). In this study, we first compared glutamate peak and steady-state EC 50 values between GluN2B wild-type and GluN2B(F637W) mutant subunits.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Previous studies showed that ethanol inhibits NMDA receptors by altering ion channel gating, primarily by decreasing mean open time of the channel, and studies from our laboratory reported that mutations at ethanol-sensitive positions in the GluN2A subunit also strongly influence ion channel gating kinetics (Ren et al , 2003a; Ren et al , 2007; Ren et al , 2008; Honse et al , 2004; Ren et al , 2013). In this study, we first compared glutamate peak and steady-state EC 50 values between GluN2B wild-type and GluN2B(F637W) mutant subunits.…”
Section: Resultsmentioning
confidence: 73%
“…For a series of mutants at GluN2A(F636), glutamate EC 50 values for steady-state current were highly correlated with those for peak current, but not with values of I ss :I p (Ren et al , 2013). In the present study, we observed that peak current glutamate EC 50 values were strongly correlated with steady-state current glutamate EC 50 values ( R 2 = 0.95, P < 0.0001; Fig 7A).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations